Betrayers [large type] : a Nameless Detective novel - Pronzini, Bill (Pronzini, Bill. "Nameless Detective" mysteries., 2010)
There are seven deadly sins, but not on the list is the deadliest of them all: Betrayal. For each of the detectives at the agency, a betrayal becomes the driving force behind an investigation and the source of the kind of resolve that can't be derailed. Tamara's investigation of a former lover uncovers a charity-bilking scam. Nameless exposes the ugly side of family. And Runyon is being confronted by a demon trying to force him into a betrayal.